Hubungan Tingkat Literasi Hukum Kesehatan Reproduksi dengan Kesiapan Pernikahan pada Calon Pengantin - Evi Zulfiana; Nora Rahmanindar (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2026)
Marriage readiness is an important aspect in forming a healthy and quality family, influenced by physical, psychological, social, economic readiness, and reproductive health. One factor thought to play a role is reproductive health legal literacy, defined as the ability to understand rights, obligations, and legal regulations related to reproductive health services. This study aimed to analyze the relationship between reproductive health legal literacy and marriage readiness among prospective brides and grooms in the working area of Lebaksiu Health Center, Tegal Regency. This analytical quantitative study used a cross-sectional approach involving 80 prospective brides and grooms selected through purposive sampling. Data were collected using questionnaires and analyzed using univariate and bivariate methods with the Chi-Square test in SPSS. Most respondents were aged 21–35 years (75%), had senior high school education (62.5%), worked in the private sector (50%), and had low reproductive health legal literacy (62.5%) and low marriage readiness (68.8%). Chi-Square analysis showed a significant relationship between reproductive health legal literacy and marriage readiness (p = 0.000; p < 0.05). Strengthening reproductive health legal literacy should be integrated into marriage guidance programs and health services to improve marriage readiness and support healthy, quality families.